Outside-In Repair of Longitudinal Tear of Medial Meniscus: Suture Shuttle Technique - Amit Joshi, M.S. (Ortho); Bibek Basukala, M.S. (Ortho); Nagmani Singh, M.S. (Ortho); Bhadra Hama, M.S. (Ortho); Rohit Bista, M.S. (Ortho); Ishor Pradhan, M.S. (Ortho) (Arthroscopy Techniques, 2020)
Meniscal tears are commonly encountered conditions of the knee. In the past, torn menisci were treated by excision of the loose flap. A better understanding of the meniscus anatomy and its biomechanical characteristics has led to the concept of meniscus preservation in eligible cases. Several suture-based repair techniques have been described in literature, including the outside-in technique. Although the outside-in technique of meniscus repair is commonly indicated for the anterior two-thirds of the meniscus, it can be used to repair the posterior part of the meniscus as well. Several modifications of this technique have been described in the literature. We hereby describe our modification of the outside-in technique of meniscus repair with the help of an epidural needle and high-strength sutures that is readily available in operating rooms. The advantages of our technique are that no large incision is required around knee joint, it's inexpensive, it can be performed with basic instruments, and even the tear of meniscus extending up to the posterior horn can be repaired. A supplemental video demonstration of the technique is included with this article.